Toward a Realist Ethics of Intervention - Wesley, Michael (Ethics & international affairs, 2005)
Since the September 11 attacks, a new security agenda has swept aside much of the old sensitivity and apathy about intervening in “failing” states. The war on terror has redefined “governance” from concentrating on issues of economic viability and popular rights to a focus on the capacity of states to generate sufficient “order” to deter or capture the agents of the new transnational security threats: terrorists, smugglers, money launderers, the carriers of zoonotic disease. As part of this process, the governance standards of other states became part of Western states' own security agendas, generating new, self-interested incentives for aid and intervention. In this article, I explore the possibilities for developing a realist-informed normative framework for humanitarian intervention in the context of the post–September 11international concern with transnational threats.